Metabolic control and its relationship with peripheral arterial disease in subjects with type 2 diabetes mellitus: A matched case-control study. - Quijandría-Cárdenas, Giuliana (2022)
Objective: To assess the relationship between metabolic control and peripheral arterial disease (PAD) in patients with type 2 diabetes mellitus (DM2) in Maria Auxiliadora Hospital (MAH). Material and methods: This is a sex-matched case-control study with a secondary analysis based on data from the endocrinology service of MAH, Lima, Peru. Cases with PAD were defined as those with <0.9 ankle-to-arm index (ATAI). Controls were those subjects with ATAI between 0.9 and 1.3, under a 4:1 relationship with respect to cases. Poor metabolic control was defined as follows: glycated hemoglobin ≥7%, systolic blood pressure ≥140 mm Hg, diastolic blood pressure ≥90 mm Hg, HDL cholesterol <40 mg/dL (males) or >50 mg/dL (females), LDL cholesterol ≥100 mg/dL and triglycerides ≥150 mg/dL. Odds ratio values for poor metabolic control were calculated, both crude and adjusted, according to the presence or PAD, by using logistic regression. Results: We included 39 cases and 157 controls. A great majority of cases (94.9%) and of controls (82.2%) had poor metabolic control, respectively (p<0.05). When adjusting for age, time with diabetes, body mass index, and history of tobacco use, patients with poor metabolic control had OR at 5.45 (95% CI: 1.17 – 25.2) and p= 0.030 for having peripheral arterial disease, as defined by ATAI <0.9. Conclusion: Poor metabolic control showed and independent relationship with PAD in DM2 patients in Maria Auxiliadora Hospital. If therapy was only centered in glycemic control, it would increase the burden of disease of macrovascular complications.